STEM AND BLENDED LEARNING FOR ENHANCING CRITICAL THINKING AND COLLABORATION - Shahina Shukhratova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This  article  explores  the  integration  of  STEM  (Science,  Technology, Engineering,  and  Mathematics)  education  with  blended  learning  approaches  to enhance  critical  thinking  and  collaboration  among  students.  By  reviewing  existing literature  and  employing  a  mixed-methods  research  design,  this  study  identifies effective strategies and methodologies for implementing blended learning in STEM classrooms. The findings indicate that blended learning environments foster deeper engagement,  promote  collaborative  problem-solving,  and  enhance  critical  thinking skills. This paper concludes with recommendations for educators and policymakers to support the adoption of blended learning in STEM education.